The “Podus” complex: New species and notes on some Acanthocinini (Coleoptera, Cerambycidae, Lamiinae) - Nascimento, Francisco E. De L.; Santos-Silva, Antonio (Zootaxa, 2019)
The males of Tropanisopodus tachira Monné & Monné, 2007, from Colombia and Paranisopodus granulosus Monné & Monné, 2007, from Peru are described for the first time. Anisopodus cochabambaensis Schmid, 2016 is newly recorded for Colombia. Tropanisopodus antonkozlovi sp. nov. is described, and a key to species of Tropanisopodus is provided. Anisopodus acutus Thomson, 1865 is transferred to Paranisopodus Monné & Martins, 1976. The female of Paranisopodus heterotarsus Monné & Martins, 1976 is described for the first time. Paranisopodus antonkozlovi sp. nov. is described and included in a previous key.